(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Puspitaningtyas DM, Handini E. 2021. Seed germination evaluation of Phalaenopsis amabilis in various media for long-term conservation. Biodiversitas 22: 5231-5238. Phalaenopsis amabilis (L.) Blume (moon orchid) is one of Indonesia’s national flowers, which is mentioned in Presidential Decree No. 4/1993. Study on the orchid seed of P. amabilis was conducted to observe the longevity of seeds storage. The purpose of this study was to determine the viability of P. amabilis seeds after storage for years, then to predict the life span of the seeds, and to find out the best media germination for P. amabilis seeds. After harvesting, P. amabilis seeds were stored at –20 °C and the germination tests were carried out periodically in different periods until the seeds lose their viability to determine the optimum conditions for long-term seed storage. Four trial media cultures have been used to test seed germination by means of in vitro culture. The result showed that seeds of P. amabilis were able to germinate in 4 media i.e. Knudson C, modified Knudson C, modified Vacin & Went and modified leaf fertilizer. The best germination was on leaf fertilizer medium. Based on the research showed that the viability seeds of P. amabilis decreased sharply after 6 years stored. By using regression analysis, the life span of the seeds could be predicted can reach 9 years of storage which is sowing on the best media (leaf fertilizer).